2018
DOI: 10.1039/c7ra11260b
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition and bonding properties of high-pressure polymeric CaN3

Abstract: Two new monoclinic P1̄-CaN3 and C2/m-CaN3 are predicted to become energetically stable under low pressure. For the first time, we identify one novel phase featuring charged “N6” chain in the P1̄-CaN3 structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…High pressure has been proven to be a powerful approach which makes the nitrogen molecular phase transform to various types of nonmolecular phases. Exhilaratingly, various polymeric structures of nitrogen in a binary system had been found using high-pressure methods in the past decade. One-dimensional infinite polymeric nitrogen chains are found in N–H, Mg–N, , CaN, , Li–N, Hf–N, Rb–N, K–N, and boron nitride nanotubes . Various nitrogen rings are found in Mg–N, , Ca–N, , Li–N, ,− Rb–N, K–N, and CsN. , Besides infinite chains and rings, nitrogen can also form many special polymeric forms such as the oligomeric N-chains in Al–N, H–N, and Cs–N; 2D network in K–N and Li–N; and 3D network in Be–N and He–N .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High pressure has been proven to be a powerful approach which makes the nitrogen molecular phase transform to various types of nonmolecular phases. Exhilaratingly, various polymeric structures of nitrogen in a binary system had been found using high-pressure methods in the past decade. One-dimensional infinite polymeric nitrogen chains are found in N–H, Mg–N, , CaN, , Li–N, Hf–N, Rb–N, K–N, and boron nitride nanotubes . Various nitrogen rings are found in Mg–N, , Ca–N, , Li–N, ,− Rb–N, K–N, and CsN. , Besides infinite chains and rings, nitrogen can also form many special polymeric forms such as the oligomeric N-chains in Al–N, H–N, and Cs–N; 2D network in K–N and Li–N; and 3D network in Be–N and He–N .…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional infinite polymeric nitrogen chains are found in N–H, Mg–N, , CaN, , Li–N, Hf–N, Rb–N, K–N, and boron nitride nanotubes . Various nitrogen rings are found in Mg–N, , Ca–N, , Li–N, ,− Rb–N, K–N, and CsN. , Besides infinite chains and rings, nitrogen can also form many special polymeric forms such as the oligomeric N-chains in Al–N, H–N, and Cs–N; 2D network in K–N and Li–N; and 3D network in Be–N and He–N . These compounds composed of polymeric nitrogen all carry a higher energy density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1980, Vogler et al [28] first reported the experimental synthesis of a neutral hexazine ring, or hexaazabenzene, through the photolysis of cis-[Pt(N3)2(PPh3)2] at 77 K. However, this claim was later ruled improbable as theoretical calculations demonstrated that hexaazabenzene would decompose into three N2 molecules due to the lack of an activation barrier [29]. Since then, a plethora of theoretical calculations has been performed to identify potential pathways to stabilise a hexazine ring as well as its most favorable geometry [30,31,[40][41][42][43][44][32][33][34][35][36][37][38][39]. Although a variety of configurations were proposed, one that stands out from others is the aromatic hexazine anion [N6] 4- [30,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The good gravimetric energy density of Fdd2-BeN 10 (5.39 kJ/g), Fdd2-MgN 10 (3.48 kJ/g) and Cc-AlN 15 (5.31 kJ/g) makes them the potential (HEDMs). The novel N 6 ring structures are found in MN 3 (M = Cs, Ca, Sr, K, Mg) [ 26 , 27 , 28 , 34 , 35 , 36 , 37 , 38 ] and MN 6 (M = W) compounds [ 39 , 40 ]. Among them, the P-1-MgN 3 phase with the N 6 ring structure is recoverable at ambient pressure [ 36 ].…”
Section: Introductionmentioning
confidence: 99%